2016
DOI: 10.1002/art.39614
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Long‐Term Outcomes Among Patients With Antineutrophil Cytoplasmic Antibody–Associated Vasculitis With Renal Disease

Abstract: Objective How advances in the management of ANCA (anti-neutrophil cytoplasmic antibody)-associated vasculitis (AAV) have impacted long-term outcomes is still unclear. We examined temporal changes over 25 years in long-term clinical outcomes, including the impact of renal function at diagnosis (a potential marker of time to disease detection) and duration of cyclophosphamide use in AAV patients with renal involvement. Methods ANCA-positive, biopsy-proven patients with AAV diagnosed in 1985–2009 followed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 36 publications
9
78
3
3
Order By: Relevance
“…This is in line with the recent studies which have shown that the long-term outcomes of patients with ANCA-associated vasculitis have improved over the last decade reflecting the changes in diagnosis and management of these patients [15,16]. The other reason could be prolonged remission maintenance therapy along with low-dose corticosteroids for up to 5 years.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in line with the recent studies which have shown that the long-term outcomes of patients with ANCA-associated vasculitis have improved over the last decade reflecting the changes in diagnosis and management of these patients [15,16]. The other reason could be prolonged remission maintenance therapy along with low-dose corticosteroids for up to 5 years.…”
Section: Discussionsupporting
confidence: 82%
“…We had a higher proportion of patients with GPA in our study compared to MPA and renal-limited disease. This is in contrast to most studies from nephrology registries which have an equal or higher proportion of MPA and RLV [15,16]. Presenting creatinine level and age had a positive correlation with mortality in a study from UK [17].…”
Section: Discussioncontrasting
confidence: 76%
“…Renal involvement in ANCA‐associated vasculitis causes necrotising crescentic glomerulonephritis often accompanied by considerable tubulointerstitial inflammation . Despite extensive treatment, a significant proportion of patients have resistant or recurrent disease activity and develop organ damage and ESRD . Markers for refractory disease activity are needed to identify patients at risk of perpetual inflammation to improve patient care and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvement in mortality and morbidity with newer treatment regimens, the risk of relapse in AAV is 35% over 5 years 3. Many patients experience persistent disease activity, long-term exposure to toxic therapies4 and the psychosocial impact of a serious illness 5…”
Section: Introductionmentioning
confidence: 99%